Marriage, Morality, and Institutional Value - Brake, Elizabeth (Ethical theory and moral practice, 2007)
This paper develops a Kantian account of the moral assessment of institutions. The problem I address is this: while a deontological theory may find that some legal institutions are required by justice, it is not obvious how such a theory can assess institutions not strictly required (or prohibited) by justice. As a starting-point, I consider intuitions that in some cases it is desirable to attribute non-consequentialist moral value to institutions not required by justice. I will argue that neither consequentialist nor virtue-ethical accounts account for these intuitions, suggesting that a distinctive deontological account is needed. The account I give is drawn from Kant’s Metaphysics of Morals; I distinguish it from Kantian views of institutions developed by Barbara Herman and Onora O’Neill. Throughout, I use marriage as an example.